Bacterial overgrowth syndrome - Yu. A. Kucheryavy; T. S. Oganesyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present the up-to-date information on pathogenesis, diagnostics and treatment of bacterial overgrowth syndrome (BOS).Original positions. Now there are no general guidelines on diagnostics of bacterial overgrowth syndrome in small intestine besides there is no common opinion which diagnostic test is preferable. Intestinoscopy with aspiration of small intestinal contents and culture of aspirate should be used in the special cases. Breath tests with carbohydrate-containing substrates (lactulose, glucose, xylose), with glycocholate, hydrogen breath test have various sensitivity and specificity. Treatment of the basic disease, that provoked development of BOS, is the most important approach. Broad-spectrum antibiotics are prescribed. Application of modern enterosorbents having cytoprotective properties is proved.